Alterations in the macrobenthic fauna from Guadarranque River (Southern Spain) associated with sediment–seawater acidification deriving from CO2 leakage. Issue 1 (15th July 2015) - Almagro-Pastor, V.; Conradi, M.; DelValls, T.A.; Riba, I.
Highlights: The impacts of CO2 -induced acidification on a macrobenthic community was evaluated. We developed a mesocosm experiment with different levels of acidified seawater. Alkalinity was demonstrated as the principal effect of seawater acidification. Results showed a different specific sensibility. Abstract: Nowadays, Carbon Storage in Sub-Seabed Geological Structures (CS-SSGS) is having much interest. Nonetheless, these technologies are still under development, especially the leakage of the stored CO2 and the consequent acidification of the environment. Therefore, the goal of this study is to test the impact of CO2 -induced acidification on a macrobenthic community due to leakages from CS-SSGS using a mesocosm-based experiment. Results confirmed the significant correlation between the abundance of the species and the pH (positively), and the alkalinity (negatively). Additionally, the BIOENV analysis showed that the majority of the variability in the abundance of the total species was explained for the alkalinity. The correlation analysis showed differential vulnerabilities of different species, especially Cyathura carinata and a non-calcifier species as Hediste diversicolor . Nevertheless, these results showed the importance of taking into account the indirect effect associated with acidification processes, as metal release from sediment.